Adsorption of Cd(II) and Fe(II) Ions by Inorganic Nanocomposites (CuO/ZnO) from Aqueous Solutions - Mohammed Khlaif Challab; Mohammad Javad Chaichi; Mohammed Turki Khathi; Omleila Nazari; Shahram Ghasemi (Indonesian Journal of Chemistry)
This research aims to investigate the nanocomposite effectiveness from CuO:ZnO-NPs at a 1:1 ratio in water-polluting heavy metals adsorption from aqueous solutions, since these heavy metals adversely affect living organisms, including cadmium and iron. The research also examines the effectiveness of heavy metal removal when influenced by parameters like pH, adsorption dose, contact duration, initial concentration, and temperature. The maximum adsorption efficiency of heavy metals reached 86.7% for Cd(II) and 84.9% for Fe(II) at 25 °C when solution conditions totaled 10 mg/L of heavy metals alongside a pH setting of 6 using 0.09 g of sorbent. The structural and physical properties of the sorbent were analyzed by atomic and FTIR, along with FE-SEM, BET, XRD, and EDX systems. This study aimed to find an economical approach for heavy metal-infused water purification and analyze water quality changes to prove the feasibility of treating these pollutants using sorbent surfaces.